Underwater holographic interferometry for structural analysis - Monteiro, J.M. (2011)
The main objective of this work was to study the application of holographic interferometry techniques to structural analysis in a underwater enviroment. These are nowadays well known techniques and with applications in different fields. However, its applications in underwater enviroments presents some new challeges. In this work it is studied the application of two techniques, ESPI and digital holography, comparing them and presenting the advantages and disavantages of each one.